2022
DOI: 10.3390/met12111846
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on the Removal and Recovery of Hazardous Cd from Cd-Containing Secondary Resources in Cu-Pb-Zn Smelting Processes

Abstract: Due to the advancement of industrialization and the development of the metal smelting industry, cadmium (Cd), as a highly toxic heavy metal element, is discharged into the natural environment in the form of dust, slag, and waste solutions during the Cu-Pb-Zn smelting process, causing great harm to the soil, water environment, and human health. Meanwhile, Cd is a key component of Ni-Cd batteries and CdTe semiconductor materials. The removal and recovery of Cd from the Cu-Pb-Zn smelting process faces a dual conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…A recent study by Selman and coauthors [6] had shown presence of high concentrations of heavy metal in the ash of incinerated waste from hospital in Iraq. Such kinds of waste material when dumped into soil, get accumulated in the environment as they are non-biodegradable [7]. Moreover, modern day hospitals are progressively using radioisotopes for diagnostic and therapeutic applications for various diseases including cancer.…”
Section: Highlightsmentioning
confidence: 99%
“…A recent study by Selman and coauthors [6] had shown presence of high concentrations of heavy metal in the ash of incinerated waste from hospital in Iraq. Such kinds of waste material when dumped into soil, get accumulated in the environment as they are non-biodegradable [7]. Moreover, modern day hospitals are progressively using radioisotopes for diagnostic and therapeutic applications for various diseases including cancer.…”
Section: Highlightsmentioning
confidence: 99%
“…Meanwhile, cadmium is widely applied in photovoltaic thin-film modules, batteries, alloy manufacturing, and plays a significant role in modern industrial development [4] . The sales price of fine cadmium in 2023 will be $5,500 per ton [5] . Therefore, the separation and recovery of cadmium in ash not only ensures the normal operation of smelting and improves the economic benefits of metal smelting enterprises but also aligns with social requirements for environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc powder is the most commonly used replacement agent in the industry, offering the advantages of strong reducibility and mild reactions [8] . At present, research on cadmium replacement mainly focuses on the replacement effect of zinc powder on cadmium solutions with low Cd 2+ concentrations [9] . However, zinc powder exhibits incomplete replacement and requires an extended processing time when used to treat solutions with cadmium ion contents up to the g/L level [10] .…”
Section: Introductionmentioning
confidence: 99%
“…However, Cd is often found in compound form within the natural environment, with surface soils containing a background concentration of 0.53 mg/kg, resulting in minimal health risks under typical environmental conditions (Liu et al, 2017). Nevertheless, Cd is found at high levels in Pb and Zn ore; thus, it is released as a byproduct during the refining of Cu, Pb, and Zn (Han et al, 2022;Min et al, 2023), meaning that the cost-effective and efficient removal of Cd from the smelting wastewater produced by the metal refining industry is of great importance.…”
Section: Introductionmentioning
confidence: 99%